Sisialisasi SIDASA (Sistem Pendataan Santri) untuk Membantu Pesantren Riyadlul 'Ulum Wadda'wah Condong Tasikmalaya dalam Mencatat Data Santri - Vepi Apiati; Siska Ryane Muslim; Linda Herawati; Ike Natalliasari (LPPM Univeristas Siliwangi, 2019)
Riyadul Ulum Wadda’wah Islamic Boarding School is located in Condong RT / RW: 01/04 Setianegara Cibeureun District, Tasikmalaya City, or about 6 km from the city center of Tasikmalaya. This boarding school belongs to one of the oldest Islamic boarding schools in Indonesia because it was founded in 1864. Its founder is KH. Nawawi from Rajapolah. The Riyadul Ulum Wadda'wah Tasikmalaya Islamic boarding school has approximately 2300 santri students, who come from various regions in Indonesia. The general objective of the implementation of the Science and Technology program for Community Development (IbBM) is to empower the community to build institutional capacity while enhancing human resources through the Santri Data System (SIDASA) in the Tasikmalaya Riyadul Ulum Islamic Boarding School based on sustainable Science and Technology. Submission of information is delivered in 3 stages, namely training in the use of software, training / emphasis on data accuracy, training in infusing students' data into the SIDASA application. The conclusions in this research are science and technology service activities for Community Development (IbBM) especially in the Riyadul Ulum Islamic Boarding School Wadda’wah Condong can provide benefits and convenience for boarding school officials in recording santri data, and can improve human resources based on science and technology